Physicochemical characterization of coconut shell liquid smoke and its potential as a natural preservative for fish balls - Mutamima, Anisa; Sunarno, Sunarno; Al'farisi, Cory Dian; Dewi, Wahyu Narulita; Trisno, Agung; Barus, Surya Danta Alberto (Universitas Lancang Kuning, 2025)
Synthetic preservatives in food products pose potential health risks and environmental concerns, leading to an increasing demand for natural alternatives. This study evaluates the physicochemical properties of liquid smoke derived from coconut shells and its potential as a natural preservative for fish balls. The production of liquid smoke involved torrefaction at 250°C, followed by purification through distillation and adsorption with activated carbon. The liquid smoke was characterized by a pH of 2.86, a density of 1.058 g/mL, and a total titratable acidity of 8.95%, meeting the Indonesian National Standard for Crude Lignocellulose Liquid Smoke (SNI 8985:2021). GC-MS analysis revealed that acetic acid (80.87%) and phenol (8.90%) were the predominant compounds, contributing to its antimicrobial properties. The efficacy of liquid smoke as a preservative was tested on fish balls at concentrations of 3%, 5%, and 7%. The best preservation effect was observed at 7% concentration, which resulted in the lowest total plate count (2.35 × 10⁶ CFU/g) after one day of storage at room temperature. These findings suggest that coconut shell-derived liquid smoke exhibits promising physicochemical characteristics and antimicrobial properties, making it a potential natural alternative to synthetic preservatives for food preservation.